Indo-Pacific parrotfish exert partner choice in interactions cleanerfish but Caribbean parrotfish do not - Soares, Marta C. (2013)
Cooperation theory puts a strong emphasis on partner control mechanisms that have evolved to stabilize cooperation against the temptation of cheating. The marine cleaning mutualism between the Indo-Pacific bluestreack cleaner wrasse, Labroides dimidiatus, and its reef fish ‘clients’ has been a model system to study partner control mechanisms and counterstrategies. These cleaners cooperate by eating ectoparasites; however, they can cheat by taking client mucus, which they prefer. Such a conflict may be the exception. For example, Caribbean cleaning gobies, Elacatinus spp., prefer to eat ectoparasites instead of mucus. While partner control mechanisms and counterstrategies seem to be absent in cleaning gobies, no study has directly compared cleaner wrasses and cleaning gobies by using the same methods. We examined systematic differences in cleaning interaction patterns and strategic behaviour exhibited by 12 closely related parrotfish species in the two systems. Parrotfish seeking cleaner wrasses visited them more often and spent more time with their cleaner than parrotfish seeking cleaning gobies. Moreover, the clients of cleaner wrasses returned more often to the same cleaner following a positive interaction, whereas the clients of cleaning gobies were less influenced by the outcome of previous interactions. We hypothesize that the higher frequency and repeated nature of interactions observed in the cleaner wrasse system, combined with the need to resolve conflicts, might have been prerequisites for the development of complex behavioural strategies.